IMPLEMENTASI PROGRAM TAHFIDZ ON THE STREET DALAM MENINGKATKAN MOTIVASI KUALITAS HAFALAN SISWA SD MUHAMMADIYAH 1 KEBOMAS GRESIK - Noris Subahul Munir; Noor Amirudin (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2026)
The rise of social media and digital technology has altered elementary students’ learning habits, including their consistency in memorizing the Qur’an. Exposure to short-form video content and digital multitasking has been shown to reduce students’ prospective memory and impair learning focus. In response, SD Muhammadiyah 1 Kebomas (SDMURI) initiated the Tahfidz On The Street program, a Qur’anic memorization activity conducted every Friday morning in the schoolyard. This study aimed to explore the program’s implementation, supporting and inhibiting factors, and its impact on students’ memorization consistency and academic achievement. Using a qualitative approach, data were collected through participant observation, in-depth interviews, and document analysis. Findings revealed that the program significantly improved students' memorization consistency, tajwid accuracy, and confidence in reciting, without disrupting academic performance. Interestingly, strong institutional support compensated for the lack of parental involvement in students’ spiritual development. This program presents a promising contextual model of tahfidz education adapted to digital-era challenges. Future research is encouraged to explore family and technology integration in strengthening students’ Qur’anic memorization.